2008
DOI: 10.1902/jop.2008.080015
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and the Risk for Non‐Fatal Stroke in Korean Adults

Abstract: Our data suggested that periodontitis is independently associated with non-fatal stroke, and its impact seems to be greater among younger or normotensive Korean adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 22 publications
1
68
0
6
Order By: Relevance
“…[1][2][3][4][5] As the periodontal tissues mount an immune inflammatory response to bacteria and their products, the systemic challenge with these agents also induces a major vascular response. The bacteria and their products evoke an immunoinflammatory reaction in the host tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] As the periodontal tissues mount an immune inflammatory response to bacteria and their products, the systemic challenge with these agents also induces a major vascular response. The bacteria and their products evoke an immunoinflammatory reaction in the host tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Acute-phase proteins, such as C-reactive protein, have been shown to be elevated in patients with periodontitis. [2][3][4] This suggests a possible influence of periodontitis on systemic status of an individual. Studies have associated periodontitis with atherosclerosis, cardiovascular diseases, and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The authors performed clinical (gingival index, BoP, probing depth, CAL) and radiological (bone loss) periodontal examinations [12,45,46,47,48,49,50]. The methodological differences were also demonstrated at the level of stroke diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sim et al, based on a group of 479 patients, established a strong link between stroke and periodontal disease in patients with CAL> 6 mm. This relationship was significant in the patients under 60 years of age with normal blood pressure [48]. Research conducted by Dorfer et al, based on the assessment of DMFT, CAL, PD, GI, PI and radiological bone loss, demonstrated that patients who have had an ischemic stroke had an increased loss of CAL, compared to the control group [49].…”
Section: State Of Knowledgementioning
confidence: 93%
See 1 more Smart Citation